Access to lexical information in language comprehension: semantics before syntax (2006)
The recognition of a word makes available its semantic and syntactic properties. Using electrophysiological recordings, we investigated whether one set of these properties is available earlier than the other set. Dutch participants saw nouns on a computer screen and performed push-button responses: In one task, grammatical gender determined response hand (left/right) and semantic category determined response execution (go/no-go). In the other task, response hand depended on semantic category, whereas response execution depended on gender. During the latter task, response preparation occurred on no-go trials, as measured by the lateralized readiness potential: Semantic information was used for response preparation before gender information inhibited this process. Furthermore, an inhibition-related N2 effect occurred earlier for inhibition by semantics than for inhibition by gender. In summary, electrophysiological measures of both response preparation and inhibition indicated that the semantic word property was available earlier than the syntactic word property when participants read single words.